Improving Reading Interest Through the Wall Magazine Program for Elementary School Students in Bajawa, Indonesia - Marselina Yolanda Bupu; Maria Patrisia Wau; Ermelinda Yosefa Awe; Dimas Qondias; Marselina Yolanda Bupu; Maria Patrisia Wau; Ermelinda Yosefa Awe (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
This study aims to determine the increase in students' reading interest through the wall magazine program at Waewaru Presidential Elementary School Technical Implementation Unit. The type of research used is descriptive qualitative research with an observation and interview approach. The subjects of the study consisted of 13 fifth grade students and the object of this study was students' reading interest at Waewaru Presidential Elementary School Technical Implementation Unit. Data collection methods were carried out through observation, interviews, and documentation. The instruments used were interview guidelines, observation sheets, and photo documentation of activities. The results of the analysis showed that the wall magazine program was effective in increasing students' reading interest. Based on observation data, the number of student visits to the wall magazine increased every day, indicating greater enthusiasm for reading. This program also encourages students' creativity in writing and conveying information, as well as strengthening collaboration between students, teachers, and parents. Thus, wall magazines can be an effective means of building a culture of literacy in elementary schools.